A Highly Reversible and Low‐Cost Sulfur‐Graphite Dual‐Ion Battery. Issue 3 (6th March 2019) - Shuai, Yi; He, Xuan; Zhang, Zeping; Chen, Kanghua; Lou, Jin; Wang, Yu; Li, Na
Abstract : The development of energy storage systems (ESSs) has received increasing attention due to the environmental degradation and fossil fuel shortage. In this study, a highly reversible sulfur‐graphite dual‐ion battery is developed, in which sulfurized polyacrylonitrile (S@PAN) is used as the anodic material. Compared with a graphite (372 mAh g −1 ) or aluminum (structural instability) anode in a dual‐ion battery, this anodic material exhibits an excellent structural stability and a high specific capacity during lithiation or delithiation. Statistically, a considerable specific capacity of 750 mAh g −1 when calculated based on the weight of S@PAN over a voltage plateau of ≈2 V with only a 7% capacity loss is achieved after 50 cycles at 100 mA g −1 and shows an attractive rate performance at different current densities. This sulfur‐graphite dual‐ion battery is considered to become a promising ESS candidate. Abstract : A dual‐ion battery is developed using sulfurized polyacrylonitrile as the anode. It is shown to provide a high discharge voltage (≈2 V) and can deliver a capacity of ≈750 mAh g −1 with a capacity retention of 93% after 50 charge–discharge cycles at 100 mA g −1 .